KEMAMPUAN LITERASI DALAM PEMBELAJARAN MEMBACA TEKS PADA SISWA KELAS VI MELALUI E-MODUL DI SD NEGERI KLOPOGODO KECAMATAN GOMBONG - Risma Puji Nalangsari; Ana Fitrotun Nisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Literacy is the ability to access, comprehend, and intelligently use something through various activities including reading, observing, listening, writing, or speaking. Reading is a process performed and utilized by readers to obtain messages conveyed by authors through written words or language. Low reading interest and difficulty in understanding difficult words in texts are the background of the study. Based on this background, the researcher developed an e-module as a teaching material. An e-module is an independent teaching material to achieve specific learning objectives that are systematically arranged into the smallest learning units, then presented in electronic form, making users more interactive with the program. The research aims to improve reading literacy skills and learning outcomes of children, as well as tools for active, creative, critical, and innovative thinking. The research method used was qualitative descriptive. The conclusion of the research is that from the validation testing by design experts and thematic learning material experts with a percentage of 92.31% and 87.49% respectively, falls within the valid category.